Razvoj storitve oddaljenega dostopa do informacijskih virov v Narodni in univerzitetni knjižnici - Vodeb, Gorazd (Knjižnica, 2006)
National and University Library established remote access to information sources in september 2004. The article describes implementation and development of the service. Library wanted to offer information sources to users wherever and whenever they would need them. First main evaluation criteria for software selection were integration with existing authentication system and second no need for intervention user side. The EZproxy software from Useful Utilities was chosen. Key step to implementation was establishing communication between software applications EZproxy and COBISS library automation system. Library needed to obtain licence agreements from publishers. Promotion campaign aimed to notify large number of users. Only users of National & University Library were able to use the service. Other users and libraries of Ljubljana University requested to authenticate by credentials of their library. Remote access service was developed further in order to enable authentication for other libraries. We needed to establish authentication and authorisation system and also upgrade and install the communication command procedure on different servers. The data about service usage are presented.
Keywords: nacionalne knjižnice; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; NUK; Ljubljana; informacijski viri; uporabniki; programska oprema